(untitled) (The East and Central African Journal of Pharmaceutical Sciences, 2018)
The practice of pharmacy has been changing over the years prompting pharmacists to explore new horizons. In many medical schools teaching of clinical pharmacology has been upgraded from the previous materia medica thus eroding the comparative advantage pharmacists previously enjoyed over their medical counterparts. Even more significant is the access to drug information on the internet at the click of a mouse. Anybody with a reasonable level of education can access reliable information on drug use, indications, dosages, mode of action, side effects, contraindications, etc. by logging onto one of the websites. Information on diagnosis and treatment of diseases has been demystified and patients may soon wonder whether health professionals are still relevant. There are still areas where pharmacists enjoy comparative advantage over other health professions. These include formulation of drugs into suitable dosage forms and quality assurance. Unless a pharmacist is working in the pharmaceutical manufacturing industry or quality control laboratory, the above advantage is of no consequence. Certainly this is the case for over 80 % of the pharmacists who work in hospitals and community/retail pharmacies. The mandatory requirement that drugs must be accompanied by adequate information, usually in form of drug literature insert has further eroded the role of hospital and dispensing pharmacists.